The Trump Effect: With No Peer Review, How Do We Know What to Really Believe on Social Media? - Brady, Justin T.; Kelly, Molly E.; Stein, Sharon L. (Clinics in Colon and Rectal Surgery, 2017)
Social media is a source of news and information for an increasing portion of the general public and physicians. The recent political election was a vivid example of how social media can be used for the rapid spread of “fake news” and that posts on social media are not subject to fact-checking or editorial review. The medical field is susceptible to propagation of misinformation, with poor differentiation between authenticated and erroneous information. Due to the presence of social “bubbles,” surgeons may not be aware of the misinformation that patients are reading, and thus, it may be difficult to counteract the false information that is seen by the general public. Medical professionals may also be prone to unrecognized spread of misinformation and must be diligent to ensure the information they share is accurate.
Keywords: social media; surgery; misinformation